Interventional cardiac catheterization in a newborn with hypoplastic left heart syndrome, severely restricted interatrial septum and cor triatriatum. (June 2014) - Fagan, Thomas; Eisdorfer, Seth; Landeck, Bruce; Howley, Lisa; Aldoss, Osamah; Twite, Mark; Jaggers, James; Ing, Richard J
An infant diagnosed by fetal echocardiography with hypoplastic left heart syndrome and suspected severe restriction of the foramen ovale developed postdelivery peripheral oxygen desaturation as low as 30% soon after transfer from the neonatal nursery to the cardiac intensive care unit. Supplemental oxygen was administered via nasal cannula and the infant underwent emergent cardiac catheterization soon after birth. The catheterization revealed cor triatriatum and an obstructed vertical vein with aberrant pulmonary venous drainage. This anatomy provided significant challenges for the anesthesia and cardiology teams. The difficulties in anesthetic, diagnostic and interventional management and decision-making in this complex anatomical diagnosis are discussed and the literature is reviewed.